Dye-collagen interactions. Mechanism, kinetic and thermodynamic analysis - Tuttolomondo, María Victoria (2015)
A large family of azo dyes have been developed and used in the textile industry, including for leather tainting, and are therefore expected to exhibit strong interactions with collagen-based materials. Here we investigate the mechanisms of adsorption of the Remazol black B dye on type I collagen hydrogel. Higher and stronger retention of the dye is achieved in alkaline conditions, correlated with enhanced thermal and mechanical stability of the hydrogel. The formation of a covalent bond between the dye and the protein network via a Michael reaction is suggested and supported by the detailed analysis of the kinetics and thermodynamics of the sorption reaction. Type I collagen hydrogels combine low cost, fast sorption, high loading and strong retention capacity together with low storage volume, making them promising materials for dye remediation. Dye-modified hydrogels may also find applications in the biomedical field.